2021
DOI: 10.1016/j.ultsonch.2021.105697
|View full text |Cite
|
Sign up to set email alerts
|

In-situ synchrotron X-ray imaging of ultrasound (US)-generated bubbles: Influence of US frequency on microbubble cavitation for membrane fouling remediation

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In 1999, Burdin et al reported that active bubbles have a typical radius of 8 μm by 20 kHz sonication as determined by laser light diffraction [39] . Also, it was reported that the average bubble radius (135 μm) at 20 kHz was about 6.8 times of that (20 μm) at 40 kHz, while the average number of bubbles at 40 kHz was about 4.6 times of that at 20 kHz [40] . In 2002, Yasui calculated the range of the ambient bubble radius with increasing ultrasonic frequency, i.e., 0.1–100 μm, 0.1–10 μm, and 0.1–3 μm at 20, 140 and 1000 kHz [38] .…”
Section: Resultsmentioning
confidence: 97%
“…In 1999, Burdin et al reported that active bubbles have a typical radius of 8 μm by 20 kHz sonication as determined by laser light diffraction [39] . Also, it was reported that the average bubble radius (135 μm) at 20 kHz was about 6.8 times of that (20 μm) at 40 kHz, while the average number of bubbles at 40 kHz was about 4.6 times of that at 20 kHz [40] . In 2002, Yasui calculated the range of the ambient bubble radius with increasing ultrasonic frequency, i.e., 0.1–100 μm, 0.1–10 μm, and 0.1–3 μm at 20, 140 and 1000 kHz [38] .…”
Section: Resultsmentioning
confidence: 97%
“…This may be attributed to the cavitation effect of ultrasound. Generally, there will be lots of tiny entrained air bubble nuclei (radius <0.1 μm) in the liquid. Under the effect of ultrasound, they could continue to grow by bubble coalescence and rectified diffusion until they collapse adiabatically. ,− The collapse of bubbles would cause shock waves, microjets, and microturbulences, which will increase the chance of collisions between lysozyme molecules, thus producing more clusters necessary for nucleation. ,,, At the same time, the enhanced micromixing can ensure a more uniform degree of supersaturation, which will result in uniform particle size distribution. Moreover, the shock waves caused by cavitation can reduce the contact between crystals, thereby reducing the probability of aggregation and encapsulation of mother liquor. , Therefore, ultrasound can effectively enhance nucleation and prevent aggregation, thereby promoting the efficient production of proteins with uniform size and regular shape.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, spherical particles were used for conjugation with HSA, rods (sphericity ratio 0.85) were used for conjugation with FB, and cylinders (sphericity ratio 0.91) were used for conjugation with TRF. Detailed information about membrane imaging and radiograph representation with membrane division into layers and regions is described in our recent papers [ 38 , 39 , 40 , 41 , 42 ]. Membrane thickness was modeled with 10 regions of interest (ROIs), as shown in Figure 2 c. Region 1 represents the very top membrane surface.…”
Section: Methodsmentioning
confidence: 99%